Use of multi-sensory marketing techniques and its influence on brand experience in retail and HORECA sector - Machala, Agnieszka (2014)
This dissertation aims at providing an analysis of the influence of sensory stimuli on consumer’s decision making process along with product and service perception. It focuses on the multisensory marketing techniques in consumer foodservice and retail sector. The impact of multisensory marketing techniques is firstly theoretically analyzed regarding advertising and in-store promotion strategies applied by FMCG and HORECA companies. The theoretical basis and conceptualization is supported by examples of successful online and offline marketing campaigns launched in recent years. The second part of this study is focused specifically on the use of multisensory promotional techniques in the foodservice environment. The real life experiment has been conducted in a local Lisbon restaurant in order to measure the influence of auditory cues on the service perception and overall customer experience. The initial hypotheses were proved by post-purchase survey conducted among patrons of the restaurant. The result of this study shows that brand, product and service perception can be positively influenced by multisensory marketing techniques. The auditory stimuli proved to be a significant source of customer overall satisfaction and in-store perception, which confirms partly the initial assumptions of the study.